Tratamento convencional e associado ao biofeedback de crianças com dissinergia do assoalho pélvico - Alice Santiago Barreto (2006)
Introduction: Approximately 50% of constipated children contract rather than relax the external sphincter complex during defecation maneuver. The biofeedback training is used to treat children with pelvic floor dyssinergia The aim of this study was evaluate the effect of conventional treatment on clinical outcome compared to conventional treatment and biofeedback training in children with pelvic floor dyssinergia.Method: Ninety constipated children with pelvic floor dyssynergia, 4 to 14years old, 64,5% male, were prospectively randomized to group 1 - conventional treatment combined with biofeedback training (45 patients) or to group 2 - conventional treatment (45 patients) and followed up during 12 months. The conventional treatment consisted of dietary advise, toilet training, oral laxatives and rectal disimpaction with enemas and the biofeedback training consisted of two to four sessions, until they normalize the anorectal function. Successful treatment was defined as 3 or more bowel movements per week, and fewer than 2 soilingepisodes per one month and no use of laxatives. Results: After six weeks of treatment, the manometric data showed decrease of thresholds of rectal sensation and increase of squeeze pressure, in both groups. Normalization of the pelvic floor dissynergia was higher in thebiofeedback group. The number of children with use of no laxatives was higher in the first group. There were no difference in bowel frequency or soiling between the two groups at follow-up. The success rate of treatment at six months follow-up was significantly higher in the first group and the normalization of the pelvic floor dyssinergia was associated with higher success rate. Conclusions: Biofeedback training combined with conventional treatment compared with conventional treatment alone result in higher success rates in chronically constipated children at 6 months of follow-up. There were good response in clinical e manometric parameters with the use of biofeedback which may be considered as na important tool in treatment of pelvic floor dyssinergia.